TANGGUNGJAWAB PENGUSAHA TAMBANG TERHADAP KESEHATAN MASYARAKAT AKIBAT DARI POLUSI YANG DITIMBULKAN - AHMAD YANI; Any Suryani Hamzah (Private Law, 2023)
This study's purpose is to determine the regulation of mining companies' social responsibility based on legislation, the causal factors of the impacts, and the company's responsibility for the resulting pollution impacts. This study uses empirical legal research methods with qualitative analysis methods through the statute approach, conceptual approach, and sociological approaches. The results of the study showed that the legislation regarding the social responsibility of mining companies are Act Number 20 of 2020 Concerning Mineral and Coal, Act Number 32 of 2009 on the environment, Act Number 36 of 2009 on health, Act Number 17 of 2019 on water resources, PMK Number 61 of 2013 on Matra Health and Government Regulation Number 22 of 2021 on the environment. the impact factors are derived from open mining activities, lack of drainage, traffic of vehicles transporting mining products and processing of open mine products without watering. The impacts include air pollution, damaged roads, the potential for soil erosion, and decreased water quality. The responsibility of the mining company for the impact caused is by watering and closing the tailgate of the mining vehicle, providing CSR, compensation to communities whose agricultural land is affected, reclamation of ex-mining land, and construction of drainage.